Morphology and in-plane thermal conductivity of hybrid graphene sheets - Reddy, C. D. (2013)
This paper investigates the morphology and in-plane thermal conductivity of hybrid graphene sheets (HGSs), which consist of un-hydrogenated and single-side or double-side hydrogenated strips, via molecular dynamics simulation. The study shows that the hydrogenation styles and hydrogen coverage significantly affect the morphology and thermal conductivity of HGSs. The thermal conductivity of HGSs decreases dramatically, compared to that of pure graphene sheets, and the magnitude falls in the range of 30%-75%. Such differences are explained by conducting the phonon spectra analysis.